E-Commerce Evolution: Trust as a Catalyst for Consumer Choices: Evolusi Perdagangan Elektronik: Kepercayaan sebagai Katalisator Pilihan Konsumen - Siti Halipah; Yuliana; Asmar Yulastri; Elida; Retnaningtyas Susanti (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the relationship between consumptive behavior and consumer confidence in online shopping and its impact on entrepreneurship in the digital era. The research method employed is a quantitative survey, which involved distributing questionnaires to 300 respondents who actively engage in online shopping. The data obtained were analyzed using validity tests, reliability tests, and multiple regression analysis to identify the influence of all independent variables. The results showed that consumptive behavior significantly affects consumer confidence, which in turn influences entrepreneurial success in the digital marketplace. This highlights the importance of understanding consumer dynamics for businesses aiming to thrive in the evolving online shopping landscape.